Determinants of Technological Innovation Adoption: An Overview of Modern Theories - MORCHID Meryeme; CHERQAOUI Mariam; ISSAMI Jihad (African Scientific Journal, 2025)
Abstract The adoption of technological innovations is a complex process influenced by various individual, social, and organizational factors. This paper provides an overview of key modern theories explaining this phenomenon. The Diffusion of Innovation Theory (Rogers, 1962) highlights the role of adopter categories and communication networks, while the Technology Acceptance Model (Davis, 1989) and the Theory of Reasoned Action (Fishbein & Ajzen, 1975) focus on cognitive perceptions and individual attitudes. The Theory of Planned Behavior (Ajzen, 1991) and its decomposed version (Taylor & Todd, 1995) introduce the concept of perceived behavioral control. More recently, the UTAUT1 and UTAUT2 models (Unified Theory of Acceptance and Use of Technology) have expanded these frameworks by incorporating additional factors such as habit, hedonic motivation, and contextual influences. Through a comparative analysis of these models, this study highlights their complementarities and limitations. It emphasizes the need for a more integrative and dynamic approach to better understand technology adoption in an ever-evolving digital landscape. Finally, the paper discusses perspectives for enhancing existing theoretical frameworks to provide a more comprehensive and adaptive understanding of technological transformations. Keywords: Technological innovation; Adoption of innovations; Determinants of adoption; Modern theories; Influential factors.